The energy spectrum of 662keV photons in a water equivalent phantom - Akar Tarim, U.; Gurler, O.; Ozmutlu, En; Yalcin, S.; Gundogdu, O.; Sharaf, Jm; Bradley, Da (Elsevier BV, 2012)
Investigation is made on the energy spectrum of photons originating from interactions of 662 keV primary gamma-ray photons emitted by a point source positioned at the centre of a water equivalent solid phantom of dimensions 19 cm×19 cm×24 cm. Peaks resulting from total energy loss (photopeak) and multiple and back scattering have been observed using a 51 mm×51 mm NaI(Tl) detector; good agreement being found between the measured and simulated response functions. The energy spectrum of the gamma photons obtained through the Monte Carlo simulation reveals local maxima at about 100 keV and 210 keV, being also observed in the experimental response function. Such spectra can be used as a method of testing the water equivalence of solid phantom media before their use for dosimetry measurements.
Keywords: 7. Clean energy